2021
DOI: 10.3390/agronomy11091702
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Herbicide Oxyfluorfen on the Activities of Some Enzymes Found in Soil and on the Populations of Soil Microorganisms

Abstract: This study assesses the effects of the herbicide oxyfluorfen on the activities of enzymes and on the populations of soil microorganisms by considering experiments on soil samples maintained in both laboratory and in field conditions. Furthermore, the molecular docking approach was used to evaluate the interactions of oxyfluorfen with enzymes found in soil. There was a dose dependent inhibitory effect of oxyfluorfen against the activities of dehydrogenase, phosphatase, protease and urease. The enzymes activitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…The results of our study and previous studies [15,25,26,31,32] indicate that herbicides were responsible for some distortion of dehydrogenase activity in soil. The analysed data revealed that clopyralid and imazamox applied in recommended doses led to a significant reduction in dehydrogenase activity at day 7 and 14 after application.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…The results of our study and previous studies [15,25,26,31,32] indicate that herbicides were responsible for some distortion of dehydrogenase activity in soil. The analysed data revealed that clopyralid and imazamox applied in recommended doses led to a significant reduction in dehydrogenase activity at day 7 and 14 after application.…”
Section: Discussionsupporting
confidence: 80%
“…In addition, no statistically significant differences were found between the investigated doses of herbicides. The impact of herbicides on dehydrogenase activity has been widely investigated with researchers mostly reporting a temporary inhibitory effect [26,32,33]. Kaur et al [34] proved that after application of imidazoline (imazamox and imazethapyr), dehydrogenase activity in soil decreased and that after a certain time, dehydrogenase activity increased.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PA was estimated on the basis of the reaction of ninhydrin with the amino acids that resulted from the hydrolysis of the gelatin used as a substrate, which was the method proposed by Drăgan-Bularda [48]. These methods have previously been applied in order to evaluate the effects on the activity of these enzymes of the herbicides aclonifen [49], S-metolachlor [50] and oxyfluorfen [51], and on the triazole fungicides triticonazole [9] and difenoconazole [52]. The soil treated with myclobutanil at different doses and the control soil were incubated for a period of 28 days under laboratory conditions, and the activity of each enzyme was determined every 7 days.…”
Section: Enzymatic Activity Analysesmentioning
confidence: 99%
“…During this process, the bacteria form a biofilm around that may help to protect them against biotic and abiotic stress and favour nutrient uptake (Rossi, 2020). In light of the above, it can be concluded that a decrease or disappearance of this bacterial function from soils due to oxyfluorfen contamination is likely to result in a marked loss of soil quality, thus preventing it from being used for agricultural purposes (Filimon et al, 2021).…”
Section: Introductionmentioning
confidence: 99%